2020
DOI: 10.1039/c9nr10745b
|View full text |Cite
|
Sign up to set email alerts
|

A hysteresis-free perovskite transistor with exceptional stability through molecular cross-linking and amine-based surface passivation

Abstract: A molecular cross-linking approach of the perovskite grains combined with amine-based surface passivation leads to hysteresis-free perovskite transistors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 49 publications
0
51
0
Order By: Relevance
“…[152] A very exciting development has been the creation of hysteresis-free devices in DPP-doped perovskite FETs by depositing polyethylenimine ethoxylated (PEIE) onto the surface of the perovskite. [152] More recently, hysteresis-free devices with high electron mobility have been developed using a different version of the triple cation perovskite (Cs 0.10 FA 0.90 Pb(I 0.83 Br 0.17 ) 3 ) doped with Rb + to passivate traps in the perovskite bulk and reduce ion migration. [52] Vasilopoulou et al used higher amounts of Rb + salts and reported only p-type operation for Rb 0.15 (MAFA) 0.85 PbI 3 .…”
Section: D Hybrid Perovskite Field-effect Transistorsmentioning
confidence: 99%
“…[152] A very exciting development has been the creation of hysteresis-free devices in DPP-doped perovskite FETs by depositing polyethylenimine ethoxylated (PEIE) onto the surface of the perovskite. [152] More recently, hysteresis-free devices with high electron mobility have been developed using a different version of the triple cation perovskite (Cs 0.10 FA 0.90 Pb(I 0.83 Br 0.17 ) 3 ) doped with Rb + to passivate traps in the perovskite bulk and reduce ion migration. [52] Vasilopoulou et al used higher amounts of Rb + salts and reported only p-type operation for Rb 0.15 (MAFA) 0.85 PbI 3 .…”
Section: D Hybrid Perovskite Field-effect Transistorsmentioning
confidence: 99%
“…Solar energy is mainly used for this due to its capacity to imitate the natural photosynthesis process to transform solar energy into chemical energy. The photocatalytic reduction of CO 2 into valued fuels like formic acid, methane, and methanol is of particular importance [234][235][236]. In the last decades, this has received great attention and we have become acquainted with the enhanced release of the greenhouse gas CO 2 into our atmosphere and the potential and real power supply shortage.…”
Section: Co 2 Reductionmentioning
confidence: 99%
“…The CO 2 reduction by photosensitive semiconductor catalysts yields highly sought products, e.g., formic acid, methane, formaldehyde, and methanol, etc. Several compounds, including metal complexes, can function as electrocatalysts for CO 2 reduction [235,236]. Bismuth and graphene's role is vital and has been studied widely in CO 2 conversion to valued products.…”
Section: Co 2 Reductionmentioning
confidence: 99%
“…As a result, nearly six years after the introduction of the PeLET concept, both conventional perovskite field‐effect transistors (FETs) and LETs cannot perform to their full potential. [ 5,13 ] So far, only a few works reported balanced ambipolar transport [ 14–17 ] or light emission from perovskite field‐effect transistors, [ 2,18–20 ] indicative of the severe limitations posed by the intrinsic transport and electroluminescence characteristics of HOIP materials.…”
Section: Introductionmentioning
confidence: 99%